Original vegetation condition and precipitation growth rate bifurcate sediment flux trend on the Qinghai-Tibet Plateau - Jinhao Guo; Yao Yue; Wenxin Huai; Xia Yan; Alistair G. L. Borthwick; Yuanfang Chai; Shuolin Li; Zhiwei Li; Yichu Wang; Chiyuan Miao; Zhonghua Yang (Communications Earth & Environment)
Abstract Riverine sediment flux on the Qinghai-Tibet Plateau follows separate trends in different headwater basins because of complicated pathways under global warming. Here we successfully reconstructed historical sediment fluxes from seven pathways at 25 hydrological stations during 1982 ~ 2022 using a conceptual Multivariate Climate Elasticity Model based on Taylor expansion and revealed the bifurcation in sediment flux trend. Significantly increasing trends occurred at five stations, caused either by elevated runoff from increased precipitation (contributing -10 ~ 50%) or by temperature modifying the underlying surface (-12 ~ 100%). Significantly decreasing trends were found at six stations, primarily owing to vegetation expansion (11 ~ 100%). Combinations of original vegetation condition and increasing rate of precipitation are pivotal for bifurcating the sediment flux trend. In the future, slowly increasing precipitation with greatly increasing temperature or poor original vegetation condition followed by rapid vegetation expansion may decelerate sediment yield, whereas rapidly increasing precipitation may overwhelm the marginal conservation effect of plentiful vegetation.